Thumb Carpometacarpal Joint Pathoanatomy—A Computed Tomography-Based Study - Al-Tawil, Karam; Garner, Madeleine; Antonios, Tony; Compson, Jonathan (Journal of Wrist Surgery, 2021)
Background Thumb carpometacarpal joint (CMCJ) osteoarthritis is common and can lead to significant morbidity making it a condition frequently treated by hand surgeons when initial conservative measures fail. The surrounding ligamentous structures are complex and important to maintain thumb CMCJ stability.Objectives The aim of this study was to review the normal and arthritic anatomy of the thumb CMCJ, focusing on morphology and position of osteophytes and the gap between metacarpal bases, and the effect of these on intermetacarpal ligament integrity. This may be the sole ligament suspending the first metacarpal following trapeziectomy and could determine the need for further stabilization during surgery, avoiding potential future failures.Methods Computed tomography (CT) scans of a normal cohort and those with arthritic changes who had undergone trapeziectomy following the scan were identified. The three-dimensional reconstructions were examined for osteophyte position on the saddle and the intermetacarpal distance.Results A total of 55 patients, 30 normal and 25 arthritic, were identified and studied. The most common anatomic position for osteophytes was the intermetacarpal ulnar aspect of the trapezium. The intermetacarpal distance increased by an average of 2.1 mm in the presence of the arthritic process.Conclusions The findings point to an increase in the intermetacarpal distance, and hence lengthening of the ligament with potential damage, possibly secondary to osteophyte formation and wear. Further prospective research is required to determine whether using preoperative CT scanning to define osteophyte position and measure the intermetacarpal distance would predict probable damage to the ligament, hence providing an indication for stabilization and reconstruction in trapeziectomy surgery.Level of Evidence This is a Level III, retrospective cohort study.
Keywords: thumb carpometacarpal joint; CMCJ arthritis; osteophyte; trapeziectomy; intermetacarpal ligament